Exploring under-exploited mango-ginger - Thanuja, G S; Krishna, V N P S; Mounika, Y; Reddy, P Syam Sundar; Singh, A K (Indian Horticulture, 2019)
Mango ginger is a unique spice having morphological resemblance to rhizomes with ginger but imparts raw mango flavour. Because of raw mango flavour, it is used as a basic ingredient in pickles, preserves, candies, sauces, curries and salad. The active phytochemical constituents present in Curcuma amada rhizome extract imparts high therapeutic properties that can prevent various infection, flatulence, jaundice, menstrual difficulties, hematuria, haemorrhage, colic and other ailments.